Game theoretic approach for channel assignment and power control with no-internal-regret learning in wireless ad hoc networks - Tan, Chee Keong; Sim, Moh Lim; Chuah, Teong Chee (The Institution of Engineering and Technology, 2008)
In wireless ad hoc networks, co-channel interference can be suppressed effectively through proper integration of channel assignment ( CA) and power control ( PC) techniques. Unlike centralised cellular networks where CA and PC can be coordinated by base stations, the integration of CA and PC into infrastructureless wireless ad hoc networks where no global information is available is more technically challenging. The authors model the CA and PC problems as a non-cooperative game, in which all wireless users jointly pick an optimal channel and power level to minimise a joint cost function. To prove the existence and uniqueness of Nash equilibrium ( NE) in the proposed non-cooperative CA and PC game (NCPG), the authors break the NCPG into a CA subgame and a PC subgame. It is shown that if NE exists in these two subgames, the existence of NE in the NCPG is ensured. Nonetheless, due to unpredictable network topology and diverse system conditions in wireless ad hoc networks, the NCPG may encounter the 'ping-pong' effect that renders NE unattainable. By incorporating a call-dropping strategy and no-internal-regret learning into the NCPG, an iterative and distributed algorithm that ensures convergence to NE is proposed. It is shown through simulation results that the proposed approach leads to convergence and results in significant improvements in power preservation and system capacity as compared with the popular distributed dynamic CA technique incorporated with PC.